Revisiting water governanceto reduce theclimate change impact on water resources in Malaysia - Md Khalid, Rasyikah; Mokhtar, Mazlin; Ab Rahman, Suhaimi (2012)
Climate change is a change in climate which is attributed directly or indirectly to human activity that alters the composition of the global atmosphere. The warming of climate has a significant impact on water resources since it has expedited ice melting and increased sea level. This intensifies hydrological cycle with more evaporation and precipitation. As Malaysia is located in the equatorial zone, rain is expected to intensify in the future. More flash flood and landslide incident is predictable in the developed areas and that will disrupt social and economic activity. As the government of Malaysia is preparing itself with strategies to mitigate and adapt the impact of climate change over water resources, question arises as to whether they are backed by adequate legal support. Up till now, both structural and non-structural measures has been implemented to cope with the impact of flood such as setting up of flood forecasting and warning systems, river basin studies, drainage master plans and hydrological and flood data collection stations. If this becomes an important national agenda, what is the role of the state governments and what are the impacts of federal decisions over states’ water resources management. This is an in depth analysis of the laws and policies on water resources and climate change. It clarifies the complex jurisdictional issues on water resources and problems that may hinder effective implementation of climate change mitigation and adaptation plans at state and local level.